Effect of Electro-Acupuncture (EA) and Manual Acupuncture (MA) on Markers of Inflammation in Knee Osteoarthritis - Shi GX; Tu JF; Wang TQ; Yang JW; Wang LQ; Lin LL; Wang Y; Li YT; Liu CZ (Journal of Pain Research, 2020)
Guang-Xia Shi,1 Jian-Feng Tu,2 Tian-Qi Wang,2 Jing-Wen Yang,2 Li-Qiong Wang,2 Lu-Lu Lin,2 Yu Wang,1 Yong-Ting Li,1 Cun-Zhi Liu2 1Department of Acupuncture and Moxibustion, Beijing Hospital of Traditional Chinese Medicine Affiliated to Capital Medical University, Beijing, People’s Republic of China; 2School of Acupuncture-Moxibustion and Tuina, Beijing University of Chinese Medicine, Beijing, People’s Republic of ChinaCorrespondence: Cun-Zhi Liu Email lcz_tg@126.comBackground: Inflammation plays a significant role in the pathogenesis of knee osteoarthritis (KOA). Although both electro-acupuncture (EA) and manual acupuncture (MA) are known to influence systemic inflammation, little is known about the potential changes in inflammation as a working mechanism of EA and MA in KOA.Methods: Data from the Acupuncture for Knee Osteoarthritis Trial (ATKOA) were used. Serum concentrations of inflammatory factors (tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), IL-6, IL-8, IL-18, IL-4, IL-10, IL-13, IL-15, IL-17, monocyte chemotactic protein-1 (MCP-1), CC-chemokine ligand 5 (CCL5), and cartilage degradation biomarkers (matrix metalloproteinase-1 MMP-1, MMP-3, MMP-13 and cartilage oligomeric matrix protein COMP)) were measured at baseline and after 8 weeks of treatment. Clinical outcomes were valid and reliable self-reported pain and function measures for osteoarthritis using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) and visual analogue scale (VAS) at baseline and post-treatment.Results: Both 8-weeks EA and MA significantly reduced pro-inflammatory cytokines (TNFα, IL-1β), and cartilage degradation biomarkers (MMP-3, MMP-13) significantly increased the anti-inflammatory cytokine IL-13 compared with pre-treatment (p< 0.05). Further, the reduction of TNF-α was more significant in EA when compared to MA (p=0.046). While there was no significant difference between groups in cytokines IL-1β (p=0.102), MMP-3 (p=0.113), MMP-13 (p=0.623) or IL-13 (p=0.935). Moreover, in both EA and MA, the effect of acupuncture on the VAS and WOMAC function scale after 8 weeks is clinically important, although no significant differences were found between groups.Conclusion: Eight weeks of both EA and MA seem to provide improvement in pain relief and function among individuals with mild to moderate knee OA. This benefit is partly mediated by changes of major inflammatory factors TNF-α, IL-1β and IL-13.Trial Registration: Controlled-Trials.com Identifier: NCT03274713.Keywords: knee osteoarthritis, electro-acupuncture, manual acupuncture, inflammation